The Effectiveness Of Using The Round House Strategy On The Cognitive Achievement Of Some Concepts In Physical Education Teaching Methods - Salwan Khalid Mahmoud (Journal Sport Science Indonesia, 2026)
This study aims to investigate differences in use of Round house strategy on cognitive achievement of certain teaching methodologies concepts for second-year students at Faculty of Physical Education and Sports Sciences, University of Mosul. The researcher hypothesized that there are statistically significant differences in average cognitive achievement scores for certain teaching methodologies concepts between experimental group, which studied using Round house strategy, and control group, which studied using traditional method. The researcher used experimental method due to its suitability to nature of research. The sample was randomly selected from two sections of second-year students at Faculty of Physical Education and Sports Sciences, University of Mosul. The experimental group consisted of section (E), while control group consisted of section (F). Homogeneity and equivalence were ensured between the groups. Curriculum for second-year teaching methods course, comprising seven semesters, was adopted. The researcher prepared an educational program that included learning units based on Round house strategy. Program consisted of eight learning units, which were studied by experimental group. Control group studied using traditional method. The researcher used necessary educational aids and techniques to implement research experiment, following tools were used to obtain results: a preliminary information form, McKinsey Multiple Intelligences Test, and a multiple-choice cognitive achievement test. The researcher concluded that students in experimental group outperformed control group in cognitive achievement, and that both Round house strategy and traditional method were effective in improving cognitive achievement. The researcher recommends using educational material prepared according to Round house strategy in teaching methods course for second-year students in faculties of physical education and sports science, and using Roundhouse strategy in teaching sports science within curricula of faculties of physical education and sports science.